Media mniejszości w procesach komunikowania społecznego - doświadczenia z terenu zachodnich województw Polski = Minority media in the processes of social communication - experiences from the area of western provinces of Poland - Mieczkowski, Janusz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Minority media are the means of communication which are available to the minority community (of the ethnic character) providing them with the presentation of their problems and evaluation of reality made by a given group. The media understood in such a way are therefore at the centre of daily practices, and generate and process the ethnic identity. The role of minority media is reflected both in institutional and functional dimension.
Keywords: mniejszości etniczne; media; województwo dolnośląskie; województwo lubuskie; województwo zachodniopomorskie